Use the four-slep process to lind \( s^{\prime}(x) \) and then find \( s^{\prime}(1), s^{\prime}(2) \), and \( s^{\prime}(3) \). \( s(x)=7 x-5 \) \( s^{\prime}(x)=\square \) (Simplify your answer. Use integers or fractions for any numbers in the expression.) \( s^{\prime}(1)=\square \) (Type an integer or a simplified fraction.) \( s^{\prime}(2)=\square \) (Type an integer or a simplified fraction.) \( s^{\prime}(3)=\square \) (Type an integer or a simplified fraction.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find \( s^{\prime}(x) \) using the four-step process, we first recognize that \( s(x) = 7x - 5 \). 1. **Identify the form**: Here, we have a linear function, which is of the form \( ax + b \). 2. **Apply the derivative rules**: The derivative of \( ax + b \) is simply \( a \). In this case, \( a = 7 \). 3. **Write the derivative**: Thus, \( s^{\prime}(x) = 7 \). 4. **Simplify**: In this case, there is no further simplification needed. So, the derivative \( s^{\prime}(x) \) is: \[ s^{\prime}(x) = 7 \] Now, we can find \( s^{\prime}(1) \), \( s^{\prime}(2) \), and \( s^{\prime}(3) \): - \( s^{\prime}(1) = 7 \) - \( s^{\prime}(2) = 7 \) - \( s^{\prime}(3) = 7 \) In conclusion: \[ s^{\prime}(x) = 7 \] \[ s^{\prime}(1) = 7 \] \[ s^{\prime}(2) = 7 \] \[ s^{\prime}(3) = 7 \]